ENTREPREURIAL SELF-EFFICACY AND THE LIKELIHOOD OF BEING SELF-EMPLOYED – A COMPARISON OF URBAN AND RURAL AREAS IN VIETNAM - Nguyen, Thi Lanh (Trường Đại học Đà Lạt, 2023)
A large body of entrepreneurship research has focused on the relationship between entrepreneurial self-efficacy and start-up activity. Yet, little is known about how the interplay of these mechanisms is moderated by informal institutional conditions (e.g., social traits in rural and urban regions). Particularly, Vietnam, a country with a socialist-oriented market economy, has emerged as one of the world’s most entrepreneurial countries. This study examines how the effects of individuals’ entrepreneurial self-efficacy on being self-employed are contingent on institutional environments (e.g., rural and urban areas). Statistical analyses of 2013 to 2015 data from the Global Entrepreneurship Monitor (GEM) project for Vietnam provide empirical evidences that entrepreneurial self-efficacy is significantly and positively associated with being self-employed, and that this effect is more pronounced for individuals in rural than those in urban areas. Moreover, the findings show that people in rural Vietnam are more willing to be self-employed than their peers in urban areas. This difference is explained by the distinct impact of the informal institutional variable, entrepreneurial self-efficacy (e.g., the knowledge, skills, and experience required to start a new business) that individuals living in rural areas may gain from entrepreneurship promotion and start-up programs supported by the Vietnamese leadership. Our findings have implications for national entrepreneurship programs and financial support for start-up projects in rural areas.